INSTITUTIONAL CHANGE, COMPETITIVE PRESSURE AND OVER-INFLUENTIAL PROFFESSORS: THE NEW JAPANESE BAR EXAMINATION - YAMAMURA, Eiji (Journal of Advanced Research in Law and Economics; Vol 1 No 1 (2010): JARLE Volume I Issue 1(1) Summer 2010, 2016)
This paper attempts to analyze the results of Japan’s new bar examination, so far held in 2006 and 2007, and to investigate why the new bar examination had unanticipated outcomes. The major findings from regression analysis are: 1. The ratio of professor committee members affects the pass rate. Further, committee members specializing in the compulsory common subjects have a more significant effect than those specializing in the selective subject areas; 2. The high pass rate for prestigious national law schools is mainly to the result of the high ratio of professor committee members, while the pass rate of private law schools is partly related; 3. Ratios of committee members from prestigious law schools at 8-22% are significantly higher than for non prestigious law schools. The unexpected outcomes that stem from the shortcomings of the new bar examination are in line with concept that high-powered incentive schemes are likely to induce behavior distortions (Jacob, and Levitt 2003). To prevent professorial cheating and to achieve fairness in the new bar examination, the Ministry of Justice should at least take steps not to appoint law schools professors as committee members.
Keywords: Competitive pressure, Japanese bar examination